Kualitas Telur yang Ditransportasikan antar Provinsi dari Sulawesi Selatan ke Sulawesi Tengah - Anas Qurniawan; Effendi Abustam; Endah Murphi Ningrum; Astati Astati; Mursidin Mursidin; Rusny Rusny; Nurfaisah Baharuddin (Musamus Journal of Livestock Science, 2022)
The large amount of poultry egg production in South Sulawesi caused the most of poultry egg seller moved their wares to some of the regions including the destination of Central Sulawesi. The transportation process was allegedly causing the decreasing of quality and quantity of eggs such as egg weight, yolk index, albumin index to location and height of the rack arrangement in the truck. The aim of thestudy was to observe and determine the effect of the location and height of the rack arrangement in the truck during transportation from Sidrap Regency, South Sulawesi to Palu City, Central Sulawesi. This research was conducted experimentally using a completely randomized design (CRD) with a factorial pattern of 3 x 5 with 3 repetitions, factor A was the location of the container in the truck diagonally and factor B was the height of the rack. The results showed that the rack location resulted in a shrinkage of 0.7%, the yolk index had no effect, while the albumin index had an effect.